ANALISIS PROSES SUKSESI PERUSAHAAN KELUARGA STUDI PADA PT PUTERASEAN - Remiasa, Marcus; Wijaya, Shelvy Anggraini (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2014)
Family business is a type of business which is most developed and dominant in the era of globalization.Ã‚Â Family business becomes one of the factors that affect the economy of a country (Poza, 2010), as the existenceof family business that should be maintained. Most of the family businesses in Indonesia have not planned theirÃ‚Â succession well. This study aims to determine what processes are carried out by PT. Puterasean for companysuccession and also to find out the performance of the company after the succession. This study uses qualitativeÃ‚Â methods. The data used is primary data which is obtained through interviews. The data validity is tested usingtriangulation techniques. The results show that PT. Puterasean processes a succession through phases ofÃ‚Â activity that are: the choice of successor candidates, development, and learning prospective successor, involvingprospective successor in the companyÃ¢â‚¬â„¢s activities, evaluation and impact on the companyÃ¢â‚¬â„¢s successor. ThisÃ‚Â study shows that the succession was going well and the involvement of the prospective successor had positiveimpact on the company as evidenced by the wide range of changes and improvement programs as well asÃ‚Â increase the companyÃ¢â‚¬â„¢s revenue.Keywords: the family business, process succession, succession post, ACE MAN